Development of Matific-Assisted Mathematics E-Modules to Increase Elementary School Students' Learning Interest - Putri Melinda Rahmawati; Ananda Nadhifah Yustikarinda; Dita Apriselia Ratna Shinta; Ummu Sholihah; Eni Setyowati (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
This study aims to develop a Matific-assisted mathematics e-module to increase elementary school students' learning interest in plane geometry. The method used is research and development (R&D) with the ADDIE model. The resulting e-module product was validated by material experts and media experts to determine the level of validity, then tested through implementation to determine the practicality and effectiveness of the product on fourth-grade students at SDIT Al-Azhar Kediri. The results of the study indicate that the Matific-assisted mathematics e-module is valid, practical, and effective to be used to increase elementary school students' learning interest. The results of the material expert validation show a percentage of 80% in the "valid" category, while the media expert validation shows 86.4% in the "very valid" category. The practicality of the e-module is shown through the results of teacher responses of 86.6% and student responses of 85.7%, both of which are in the "very practical" category. The effectiveness of the e-module was analyzed by comparing the mean value of learning interest before and after using the e-module which showed an increase from 66.94 to 80.95 with a significance value of the Paired Sample T-Test of 0.001 < 0.05 and an N-Gain value of 0.40 in the "quite effective" category.